A Proposed model on monitoring quality in call centers - Baguio, Roy Gabriel N.; Lim, Melissa Arni D.; Parale, Kristina G.; Santiago, Jennifer Marie R. (Diliman, Quezon City College of Engineering, 2005)
Quality measurement is important not only in the manufacturing industry but in the service sector as well. It is essential to the company that the quality of service or product output is measured to ensure that the company is producing the best product for the people. Quality in call centers is defined as the relationship between the customer's expectations of the service and how the customer perceives the service rendered. Ensuring good quality service in call centers is done through the individual performance of each agent. Each call center has its own method and criteria of evaluating performance, thus comparison among call centers, in terms of agents performance, is not possible. There is a need for standardization of the performance rating system to facilitate comparison amongst them and thus benchmarking would be easier. A performance rating system was constructed based on interviews and guidelines on how to develop performance rating. Each account has a different criterion which is the most important in evaluating its quality. Thus, different weights were assigned to each quality criterion for each type of account. The resulting ratings based on the proposed rating system are plotted to a coordinate system wherein the horizontal axis is the periods of rating while the vertical axis is the overall rating. This control chart embodies the visual representation of the output of the inbound sector of call centers that would be used to monitor its overall performance. Trends, patterns and variability of the quality of service will be detected and a one-sided process capability ratio with a lower specification limit will be computed. Two recommendations were proposed. One, the group recommends a wider section of call centers be consulted. The other would be to conduct an actual application of the model with the performance rating system formulated for further validation.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Call centers; Production engineering